A cry for help: Dramatherapists can intervene to change the language and environment in mental health care by engaging critically with the new diagnostic category of Complex PTSD. Issue 3 (December 2020) - Widnall, Lee-Anne
In funded healthcare settings, access to dramatherapy and other arts therapies is limited. Patients suffering the long-term emotional effects of childhood or prolonged trauma are often not helped by short-term funded therapies. These therapies that engage in the diagnostic model of suffering with disorder specific research speak little to those suffering multiple traumas. This leaves dramatherapists unable to reach those most in need of their skills. At the same time, survivors are left bewildered and shamed again as they 'fail' to benefit from the limited symptom management approaches on offer. While the diagnostic model of suffering may be approaching obsolescence, what still seems a long way away is a major overhaul of the mainstream understanding of suffering and mental health that could fuel a reorganisation of how services are delivered and research conducted. In this context, the new diagnostic criteria of Complex Post Traumatic Stress Disorder in the International Classification of Diseases-11 provides an opportunity and perhaps even a rallying cry for dramatherapists to evidence how our skills can provide a framework and method for survivors to re-imagine themselves and understand and claim their place in the world by loosening the chains of fear and shame.